Progress in Single Dish 21 cm Intensity Mapping - Anderson, Christopher Joseph (Proceedings of the Wisconsin Space Conference, 2017)
Progress has been made in finalizing the design of a 7 element array to be installed on the Green Bank Telescope in the 700 to 900 MHz frequency range.  The new array should increase HI intensity mapping speed by a factor of 4.  The design review for the array is scheduled for October 19.  At the same time, 21 cm intensity mapping data collected from the Parkes radio telescope has been analyzed.  We have detected HI signal in cross-correlation with the 2df Galaxy Survey.